THU0578 Factors Associated with Early Diagnosis of Familial Mediterranean Fever. (15th July 2016) - Tezcan, M.E.; Avcı, M.; Kalkan, N.B.; Giousouf, A.; Dasdemir Vardi, N.; Akbal, N.; Sevinc, E.; Celik, S.; Sargin, M.
Abstract : Background: Familial Mediterranean fever (FMF) is characterized by recurrent attacks of polyserositis. Delay in treatment may lead to recurrent attacks and amyloidosis. Objectives: In this study, we aimed to evaluate clinical features of patients diagnosed early and compared to those diagnosed late Methods: We enrolled 143 FMF patients over the age of 18 who met Tel-Hashomer Criterias into the study. Demographic features of the patients, duration of education, smoking habits, family history of FMF disease and amyloidosis, ; features, duration and frequency of FMF attacks; age at first FMF attack; age at first admittance to a specialist, time between first FMF attack to first admittance to a specialist and which medical specialities patients admitted for their symptoms were recorded with face to face survey method. Else, MEFV gene mutations of the patients, time between first admittance to a specialist to diagnosis, clinical decision and judgement of the specialists at the time of diagnosis were obtained from hospital's medical recording system. Early diagnosis was defined as within three years after the first symptom. Results: Mean diagnostic delay was 12.03±10.43 years. Age at first FMF attack (p=0.020), time between first FMF attack to first admittance to a specialist (p=0.003) and first admittance to a specialist after year 2000 (p=0.001) were found statistically important related with early diagnosis in a regression model. MEFV mutation was the only method that had an influence on the decision making of doctors in the diagnosis of FMF especially after year 2000. Conclusions: Instead of demographic, clinical and genetic differences, early diagnosis may related with increased patient awareness about the disease. Furthermore, availability of MEFV mutation may influence doctors' decision making positively for facilitating early diagnosis of FMF and may replace clinical features. But, this may lead to failures in diagnosis in gene-negative FMF cases. References: Ben-Chetrit, E. M. Levy (1998) Familial Mediterranean fever.Lancet 351:659–64 Livneh, A., P. Langevitz, D. Zemer, N. Zaks, S. Kees, T. Lidar, A. Migdal, S. PadehM. Pras (1997) Criteria for the diagnosis of familial Mediterranean fever.Arthritis Rheum 40:1879–85 Disclosure of Interest: None declared